Genome‐wide identification and analysis of genes associated with RNA interference in Bemisia tabaci. Issue 11 (16th April 2019) - Tian, Lixia; Zeng, Yang; Xie, Wen; Wu, Qingjun; Wang, Shaoli; Zhou, Xuguo; Zhang, Youjun
ABSTRACT: Background: As a method of RNA‐mediated gene silencing, RNA interference (RNAi) is a useful reverse genetic tool with which to study gene function, and holds great promise for pest management. Bemisia tabaci is a cosmopolitan pest that causes extensive damage to crops. The mechanism underlying RNAi efficiency in B. tabaci is not well known. We identified and analyzed candidate genes in the RNAi pathway to understand the RNAi mechanism and provide a basis for the application of RNAi in pest management. Results: We identified 33 genes putatively involved in the RNAi pathway from the B. tabaci Q genome. Phylogenetic and structural analyses confirmed the characteristics of these genes. Furthermore, quantitative real‐time reverse transcription polymerase chain reaction (qRT‐PCR) and transcriptomic analysis profiled gene expression patterns during different developmental stages. Gene expression levels estimated by qRT‐PCR and RNA‐seq analyses were significantly correlated. Moreover, gene functions were verified by RNAi. When accompanied by knockdown of AGO2, Dicer2 and Sid1, the efficiency of CYP6DB3 RNAi decreased correspondingly. Conclusion: In this study, we annotated and validated genes involved in B. tabaci RNAi. A better understanding of the building blocks of the RNAi process in B. tabaci facilitates integration of this novel biotechnology into the management of this emerging pest, either directly or indirectly. © 2019 Society of Chemical Industry Abstract : Thirty‐three RNAi genes were identified and validated from the Besimia tabaci Q genome. Dicer2, AGO2 and Sid1 were shown to influence RNAi efficiency in B. tabaci .